Impacts of the energy matrix on Brazilian sustainable development - Gehrke, Poleana; Goretti, Ana Alice Timm; Ávila, Lucas Veiga (Revista de Administração da UFSM, 2021)
Objective: Analyze the impacts of the energy matrix and its relationship with Sustainable Development. Methodology: The study is classified as descriptive composed of mixed methods, based on the results of ANEEL 2020, disclosed in the Generation Information Systems of ANEEL SIGA, and the results of EPE from the years 2015 to 2019, disclosed in the Energy Balance National. Results: As main results, it stands out: that the energy matrix of Brazil has been going through changes, especially in the last five years, taking into account the main renewable energies consumed and emerging in the market, the renewable energies in the period between 2015 and 2019 had a growth around 12%, while non-renewable energies decreased by 8.4%, however the world energy matrix is ​​unlike the Brazilian matrix, where non-renewable energies had an increase of 0.1% and renewable energies had a reduction of about 0.8%. Originality/value: With the increasing demand for energy consumption and considering environmental problems, such as global warming, the search for a cleaner energy matrix has become the focus of several research. This study aims to propose that both the Brazilian case - which is already treated as an example - as well as the world case can be explored in a more satisfactory way its energy reserves, thus adopting a diversified and efficient energy matrix, consequently reducing the environmental impacts.